Variable Pore Structure and Gas Permeability of Coal Cores after Microwave Irradiation. (6th December 2018) - Hong, Yi-du; Lin, Bai-quan; Xiang, Hua; Zhu, Chuan-jie; Wang, Zheng; Nie, Wen
Abstract : The experimental work in this paper investigated the effect of microwave energy on pore structure and gas permeability of coal cores. Fifteen coal samples were irradiated under the condition of 2.45 GHz with 6 kW. The effect of microwave irradiation on the pore structure of coal samples was evaluated by nuclear magnetic resonance (NMR). The water saturation degree has little influence on transverse relaxation time (T 2 ) distribution before the microwave treatment. By contrast, water saturation degree obviously affects theT 2 distribution after the microwave energy treatment. Coal permeability increased after microwave energy treatment. But fractal dimension decreased after microwave energy treatment. The results show that microwave energy has a potential for degassing coal seams.